Islamic schools in modern Turkey faith, politics, and education - Ozgur, Iren, 1976- (New York : Cambridge University Press, 2012)
"An analysis of Imam-Hatip schools in Turkey and how they contribute to the Islamization of the country at both the high and grassroots levels of politics"--Provided by publisher.
Machine generated contents note: 1. Imam-Hatip schools within a secular state; 2. Accumulating and exhibiting habitus; 3. Agents of political socialization: influences in the communities; 4. Imam-Hatip schools, their communities, and Islamist politics; 5. Imam-Hatip schools, their communities, and Islamist civil society organizations; 6. International interest and conclusions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Islamic religious education -- Turkey; Islam and state -- Turkey; RELIGION / Islam / General; Electronic books